The accident man : a novel - Cain, Tom (London : Corgi Books, 2008)
Samuel Carver, a master at arranging fatal'accidents' for a certain sum of money, agrees to stage an incident below a Paris bridge on August 31, 1997, only to find he has been set up and must somehow evade the very people who hired him.
Originally published: Great Britain : Bantam Books, 2007.
Keywords: Diana, -- Princess of Wales, -- 1961-1997 -- Death and burial -- Fiction; English fiction